Pokrajinskoekološka členitev Zgornje Gorenjske - Ferreira, Andreja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
The landscape-ecological methodological approach is due to its holistic approach most suitable for the study of relations between separate landscape-ecological units and their impacts on land-use and human activities.The Upper Gorenjska region was divided into 5 landscape-ecological types and 19 landscape-ecological units. Landscape-ecological types and landscape-ecological units showed a high inner differentiation of the studied area, which is not clearly detected in the existing territorial units, such as cadastral districts, councils, etc. The homogeneity of landscape-ecological types and landscape-ecological units enabled a simpler interpretation of the obtained data and, in turn, better results.
Keywords: kulturna pokrajina; pokrajinska ekologija; raba tal; regije; tipizacija; Slovenia; Slovenija; Upper Carniola; Gorenjska